2014
DOI: 10.1093/jxb/eru253
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in photosynthetic capacity, growth, and yield in 64 field-grown wheat genotypes

Abstract: SummarySignificant variation in photosynthesis and growth in 64 wheat cultivars was explained by differences in photosynthetic capacity, operation and CO2 diffusion. Natural variation in photosynthesis is an underutilized resource for potential crop improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
234
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(256 citation statements)
references
References 60 publications
(89 reference statements)
8
234
5
Order By: Relevance
“…Differential hybrid performance for gas exchange WUE at normal densities and positive correlation with PYE was also encouraging. Driever et al (2014) suggested that natural variation in photosynthetic capacity is a currently unexploited genetic resource and could be used for potential crop improvement (Lawson and Blatt, 2014;Tardieu et al, 2014;Ge et al, 2012). Synchronization of pollen and silk emergence is presumably important under water stress conditions; thus, the negative relationship of PYE with ASI also supports this.…”
Section: Discussionmentioning
confidence: 99%
“…Differential hybrid performance for gas exchange WUE at normal densities and positive correlation with PYE was also encouraging. Driever et al (2014) suggested that natural variation in photosynthetic capacity is a currently unexploited genetic resource and could be used for potential crop improvement (Lawson and Blatt, 2014;Tardieu et al, 2014;Ge et al, 2012). Synchronization of pollen and silk emergence is presumably important under water stress conditions; thus, the negative relationship of PYE with ASI also supports this.…”
Section: Discussionmentioning
confidence: 99%
“…Plant harvest and flag leaf preparation was carried out according to the methodology described by [27]. Leaf gas exchange parameters were measured at an ambient CO 2 concentration of 400 µmol CO 2 µmol air −1 ; light levels (Photosynthetic Photon Flux Density, PPFD) of 1800, 1000, 500, 250, and 100 µmol photons m −2 s −1 ; a vapour pressure deficit of 0.9 kPa; and a block temperature of 20 • C. Maximum net photosynthesis (Amax) was measured at 1200 µmol CO 2 µmol air −1 and 1800 µmol photons m −2 s −1 .…”
Section: Phenotypingmentioning
confidence: 99%
“…However, phenotyping leaf gas-exchange traits in detail for large populations under field-grown conditions can be challenging, given the length of time taken to perform the measurements and the plant responses to climatic conditions and circadian rhythms. In the current work, the methodology proposed by [27] contributed to standardizing measuring conditions and allowed a reliable method to assess gas-exchange traits in field grown plants. Despite the improved methodology, measuring gas-exchange at the leaf level, using infra-red gas analysers (IRGAs), is still a time-consuming process.…”
Section: Canopy Vs Leaf Photosynthesismentioning
confidence: 99%
“…Moreover, another study reported that large LA (flag leaf) in two contrasting barley populations resulted in higher grain yield because of higher photosynthetic rates under field conditions [19]. LA and its position in the canopy have an effect on the relationship between cereal growth, yield, and photosynthesis [20] and maximizing photosynthetic rate could be achieved by expanding LA in rice and wheat [21,22]. Manipulating LA to increase grain yield would be beneficial for future breeding programs [13,23]; however, LA manipulation in barley did not succeed because of low heritability which did not permit effective genetic manipulation.…”
Section: Introductionmentioning
confidence: 99%